Regulation of dally, an integral membrane proteoglycan, and its function during adult sensory organ formation of Drosophila. - Fujise, M.; Izumi, S.; Selleck, S.B.; Nakato, H. (Developmental Biology, 2001)
In Drosophila, imaginal wing discs, Wg and Dpp, play important roles in the development of sensory organs. These secreted growth factors govern the positions of sensory bristles by regulating the expression of achaete-scute (ac-sc), genes affecting neuronal precursor cell identity. Earlier studies have shown that Dally, an integral membrane, heparan sulfate-modified proteoglycan, affects both Wg and Dpp signaling in a tissue-specific manner. Here, we show that dally is required for the development of specific chemosensory and mechanosensory organs in the wing and notum. dally enhancer trap is expressed at the anteroposterior and dorsoventral boundaries of the wing pouch, under the control of hh and wg, respectively. dally affects the specification of proneural clusters for dally-sensitive bristles and shows genetic interactions with either wg or dpp signaling components for distinct sensory bristles. These findings suggest that dally can differentially regulate Wg- or Dpp-directed patterning during sensory organ assembly. We have also determined that, for pSA, a bristle on the lateral notum, dally shows genetic interactions with iroquois complex (IRO-C), a gene complex affecting ac-sc expression. Consistent with this interaction, dally mutants show markedly reduced expression of an iro::lacZ reporter. These findings establish dally as an important regulator of sensory organ formation via Wg- and Dpp-mediated specification of proneural clusters.